Modelagem da intrusão salina utilizando analise de sensitividade adjunta – estudo de caso: CAP-BON/Tunisia - Rocha, Erika da Justa Teixeira (2011)
Today the water is a natural well which limits the socioeconomic development and even the subsistence of the population. An attempt to minimize the problem of water scarcity has used the farming of groundwater. However, this growth of the use of groundwater was done inappropriately and with inadequate wells construction. This practice was eventually put at risk the quality of groundwater. Thus, the management of groundwater resources has become a major challenge. This thesis proposes developing a model for the simulation of water flow and mass transport for transient problems in coastal aquifers subject to saline intrusion, through the development of a numerical model. Then we developed a sensitivity analysis with the goal of enabling through better knowledge of local parameters and their influences, a best fit of model to reality.